Experimental study on temperature variation of metal hydride reactor incorporating helically coiled heat exchanger during absorption. (15th December 2021) - Bao, Zewei; Mou, Xiaofeng
Highlights: An experimental set-up for metal hydride reactor with helical coiled tube was built. Increasing hydrogen pressure makes time variations of bed temperature more unevenly. Low fluid outlet temperature limits heating utilization at low fluid inlet temperature. The recommended fluid velocity (1–3 m/s) inside heat exchanger tube is not suitable. The hydrogen absorption process can be controlled by changing hydrogen flow rate. Abstract: Incorporating the helically coiled heat exchanger (HCHE) into the metal hydride (MH) reactors is an effective way to improve the hydrogen absorption rate. In the present study, an MH reactor incorporating a HCHE was built to investigate the influences of various operating parameters on the bed temperature and the heat transfer fluid outlet temperature at the hydrogen supply pressure ( p s ) of 0.8–1.2 MPa, the fluid inlet temperature ( T in ) of 20–40 °C, and the fluid flow rate ( qf ) of 10–50 L h −1 . The experimental results show that the increase in the p s and qf can improve the heat transfer performance and accelerate the hydrogen absorption process. Nevertheless, increasing p s makes the temporal variations of the bed temperature and fluid outlet temperature more unevenly, which limits the utilization for the heating system. Furthermore, the recommended fluid velocity (1.0–3.0 m s −1 ) inside heat exchanger tubes is not suitable for the MH reactor design. Compared with the hydrogen supply at constant pressure, the highest values of the MH bed temperature and the fluid outlet temperature rise are lower at constant flow rate of hydrogen. In addition, the hydrogen absorption process can be controlled by changing the hydrogen flow rate.